Femoral Neck Shortening After Hip Fracture Fixation Is Associated With Inferior Hip Function: Results From the FAITH Trial. Issue 10 (October 2019) - Felton, Jessica; Slobogean, Gerard P.; Jackson, Sarah S.; Della Rocca, Gregory J.; Liew, Susan; Haverlag, Robert; Jeray, Kyle J.; Sprague, Sheila A.; O'Hara, Nathan N.; Swiontkowski, Marc; Bhandari, Mohit
Abstract : Objective: To describe the distribution of femoral neck shortening after internal fixation and to determine whether shortening is associated with inferior hip function at 24 months after a hip fracture in patients 50 years of age or older. Design: Retrospective cohort study. Setting: A secondary analysis of data from 81 clinical centers included in the Fixation using Alternative Implants for the Treatment of Hip Fractures (FAITH) trial. Participants: Three hundred fifty patients, 50 years of age or older, who had an isolated femoral neck fracture and underwent timely operative fixation of the fracture. Intervention: Femoral neck shortening was measured as a categorical variable and classified into one of the following groups, as determined by the Central Adjudication Committee: no shortening, mild shortening (⩽5 mm), moderate shortening (6–10 mm), or severe shortening (>10 mm). Main Outcome Measurement: The primary outcome for the current analysis was hip function, as measured by the Western Ontario & McMaster Universities Osteoarthritis Index questionnaire, at 24 months after injury. Results: Two-thirds of patients had no or mild shortening (⩽5 mm), whereas one-third of patients had moderate or severe shortening (>5 mm). After adjusting for surgical treatment, a greater amount of femoral neck shortening was found to be associated with poorer hip function ( P < 0.01). Conclusions: We found that increasing femoral neck shortening was associated with inferior hip function. Although internal fixation often results in successful union, patients who heal in a shortened position report poorer functional outcomes. Level of Evidence: Prognostic Level II. See Instructions for Authors for a complete description of levels of evidence.